Human Resources for Health: Availability and Competencies for Maternal and Newborn Health Care Services - Sodani, Prahlad Rai; Sharma, Kalpa (National Journal of Community Medicine, 2013)
Background: Human resources are the largest component of health care delivery system in India and motivated health workers are essential for improving health outcomes. Objectives: The objective of this paper is to study the availability and competency of staff at community health centers (CHCs) and 24X7 primary health centers (PHCs) and compare these with the Indian Public Health Standards (IPHS). Materials and Methods: Data were collected from various health service providers and managers at district, block and community level through well structured questionnaire. Results: Shortage of manpower especially specialists were observed at CHCs whereas at 24*7 PHC shortage of laboratory technician and pharmacist were observed. More than 75 percent medical officers were competent in history taking and physical examination during ANC followed by antenatal counseling and interventions (71.4%), health education and counseling (66.7%) and providing newborn care (61.9%) whereas nearly 70 percent of the nursing staff were competent in ANC history taking, establish I/V line and give fluid and conduct normal delivery. Fourteen programme managers found themselves competent in monitoring and evaluation followed by implementation planning (76.5%), managing training programmes (76.5%), programme management and review (58.8%), quality management (58.8%), essential computer skills (58.8%), developing action plan (58.8%) and managing contracts (58.8%). Conclusions: Important deficiencies were revealed in the studied CHCs and 24X7 PHCs of Bharatpur district and by additional inputs such as recruiting staff health facilities can be upgraded. Training is essential for enhancing the competencies which should be addressed on the priority basis.